The Association Between Social Media Use and Urinary Tract Infections in Children - Algutaini, Safana Abdullah; Atween, Ayad; B. Hall, Marla (Journal of Medical Health Research and Psychiatry, 2024)
Background: The proliferation of social media platforms has fundamentally altered the daily behaviors of children and adolescents. In turn, concerns about its potential impact on physical health, including Urinary Tract Infections (UTIs), are evident. This study explored the relationship between social media use and UTI incidence in children aged 2-17 years, aiming to identify patterns of risk and potential preventive measures. Methods: A cross-sectional study was conducted in which 500 parents or guardians of children who used social media were recruited. Participants were recruited through a combination of mini lectures at universities, in-depth interviews with parents at community centers and pediatric clinics, and online posts on social media platforms. A structured questionnaire was administered to gather data on social media usage patterns, bathroom habits, fluid intake, and UTI history. Descriptive statistics were used to summarize the data, while Pearson’s correlation and chi-square tests were employed to examine the associations between social media use, platform-specific usage, gender, fluid intake, and UTI incidence. Results: A total of 37% of the children had experienced a UTI in the past year. There was a modest positive correlation between prolonged social media use and UTI incidence (r = 0.093, p < 0.05). Children who used social media more than 4 hours per day exhibited significantly greater UTI rates, with incidence rates of 46.6% for 4-6 hours and 45.5% for more than 6 hours of daily use. Platform-specific analysis revealed that TikTok users had the highest UTI incidence (81.2%), followed by Snapchat users (56.8%). Gender analysis revealed slightly greater UTI rates in males (36.4%) then in females (34.0%), although the difference was not statistically significant (p > 0.05). Unexpectedly, children who consumed more than 8 glasses of water daily also exhibited a higher UTI incidence (55.6%), suggesting potential underlying health or behavioral factors that warrant further investigation. Conclusion: This study highlights the potential link between excessive social media use and an increased risk of UTIs in children, particularly among users of highly immersive platforms such as TikTok and Snapchat. The findings suggest that prolonged digital engagement may contribute to health risks by influencing behaviors such as delayed bathroom visits and inadequate hydration. These results underscore the importance of balanced digital habits and active parental involvement in managing children’s social media use. Therefore, public health initiatives should focus on educating parents and children about the potential health risks associated with excessive screen time and promoting healthier digital practices. Implications: The findings of this study have significant implications for public health strategies aimed at promoting digital wellness among children and adolescents. However, further research is needed to explore the causal mechanisms underlying the observed associations and develop interventions that can effectively mitigate the health risks associated with prolonged social media use.